DNAseq of S. coelicolor foraging sectors - Sandblad, Linda; Söderholm, Niklas (Umeå University, 2024)
S. coelicolor was inoculated on FAM and incubated for 20 days at 30°C, to allow for sectors to form. the sectors were isolated and grown in TSB media and 600 mg pellet was collected and sent to MicrobesNG for DNA preparation and Illumina sequencing. Trimmed (Trimmomatic) and quality checked reads (using MicrobesNG in-house scripts combined with Samtools BedTools, and bwa-mem) were returned for (i) inoculum "WTparental", (ii) first level sector "alpha"/"A0", (iii) second levels sectors "I"/"A1" and "IV"/"A4".
Keywords: Bacteriology; Sequence analysis; Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik; Biological Sciences; Biologi